From Loan Sharks to Commercial Banks: Moral Crusades and the Segmentation of the Credit Market in the United States, 1900-1945 - Simon Bittmann (Revue de la Régulation)
The segmentation of the American credit market, between a primary banking market and a secondary “fringe” market, characterized by high-rate services offered by credit agencies ranging from payday lenders to subprime mortgage dealers, is often mentioned and bemoaned, particularly as it would mirror the structure of the dual labor market, and yet very few studies are dedicated to understanding its origins. This dissertation offers such a perspective through the study of one specific type of credit transactions, in the form of small unsecured loans to different types of wageearners. First, we study the emergence of new credit systems at the beginning of the XXth century, which enabled lower-class workers to borrow using their future wages or small property as collateral.Two case studies focusing on the South and the Midwest enable us to set forth a new, more intersectional conceptualization of the credit relationship: we underline the different forms of embeddedness of these exchange systems, particularly in the labor process, in the judicial system and in specific forms of racial segregation. Second, our research analyses the moral and political construction of a legitimate “business” of unsecured lending, through the study of the crusades and controversies targeting “loan sharks”, a certain class of creditors which gravitated on the fringe of industrial capitalism until the mid-1940s. This work in economic sociology contributes to a growing body of studies of market moralization processes, but it relies on insights from the sociology of organization, public action, social movements and law in order to understand more precisely how the resolution of a public problem, and the legal evolution it produces, as well as the frames and normative settings on which political action dwells, can impact the shape and the structure of the market. Our theoretical framework thus tries to bridge the gap between the sociological study of economic transactions, practices and contracts and the political-cultural approach of markets as politics, a separation often criticized by French and American sociologists alike.